The Role of the Social Judge in Adapting the New Circumstances Related to Employment Contracts (An Analytical Study in the Light of Provisions Learned from the Corona Pandemic) - Belbaki, Boumediene (Journal of Legal Studies and Researches, 2024)
This study aims to take advantage of the legal provisions approved by the legislator in light of the Corona pandemic, in order to face any emerging circumstance in the future that may threaten the legal positions of the parties to the work relationship. As a result, to achieve a degree of legal protection for the rights of the parties, by restoring the contractual balance of work's relationships.